1982
DOI: 10.1142/s0192415x82000166
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Davallina Orientalis on Bone Healing — A Preliminary Report

Abstract: A crude methanol extract of the herb Davallina Orientalis was given intraperitoneally to test its effect on bone healing in mice. The results indicated that it could increase the breaking strength of a fracture site. In our experimental model, the lower dosage has a better result probably because of less toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Only 25.81% ( n = 8) [22, 32, 37, 38, 42, 46, 48, 49] reported whether the fracture had complete, partial, or absent closure. Other analyses related to bone strength, tensile strength, and expression of inflammatory genes that stimulate bone formation and osteogenic differentiation were performed in 38.71% ( n = 12) of the studies [20, 23, 24, 28, 33, 36, 40–42, 44, 45, 47] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Only 25.81% ( n = 8) [22, 32, 37, 38, 42, 46, 48, 49] reported whether the fracture had complete, partial, or absent closure. Other analyses related to bone strength, tensile strength, and expression of inflammatory genes that stimulate bone formation and osteogenic differentiation were performed in 38.71% ( n = 12) of the studies [20, 23, 24, 28, 33, 36, 40–42, 44, 45, 47] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…CHMs may exhibit bone protection effect after longterm treatment. Studies have also suggested that CHM may be beneficial for bone metabolism through osteopenia prevention, anti-osteoporotic activities, promotion of fracture healing, and inhibition of inflammation (Chow et al, 1982;Chen et al, 2005;Li et al, 2011;Ma et al, 2011;Xiang et al, 2011;Wong et al, 2013;He and Shen, 2014;Zhang et al, 2016;Hsiao et al, 2017;Wang et al, 2018b;Xi et al, 2018;Lee et al, 2019). Among these studies, there were two review studies reported in human beings.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbal medicines (CHMs) are often used to treat bone related diseases, as they show anti-inflammatory, antiosteopenia, anti-osteoporotic, and promote fracture healing activities (Chow et al, 1982;Chen et al, 2005;Li et al, 2011;Ma et al, 2011;Xiang et al, 2011;Shih et al, 2012;Wong et al, 2013;He and Shen, 2014;Mukwaya et al, 2014;Lin et al, 2015;Zhang et al, 2016;Hsiao et al, 2017;Wang et al, 2018b;Xi et al, 2018;Cheng et al, 2019a;Cheng et al, 2019b). However, none of these studies have been carried out in prospective randomized clinical trials in humans.…”
Section: Introductionmentioning
confidence: 99%
“…As CHM is cost-effective with relatively few side effects and has been widely applied for clinical use in Asian countries, it has been previously used for the clinical treatment of osteoporosis and bone fracture in Taiwan (Shih et al, 2012; Liao et al, 2015). Indeed, there are several Chinese herbs that help maintain bone health by regulating bone metabolism (Chow et al, 1982; Chen et al, 2005; Li et al, 2011; Ma et al, 2011; Xiang et al, 2011; Wong et al, 2013; He and Shen, 2014; Zhang et al, 2016; Hsiao et al, 2017; Wang et al, 2018c; Xi et al, 2018). Our pharmacoepidemiologic results have demonstrated that for the patients who were above 60 years old, there was a significant distribution difference in the cumulative overall mortality between CHM and non-CHM users ( Table S3 and Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…CHM has also been used to treat bone-related diseases including osteoporosis and bone fractures (Shih et al, 2012; Mukwaya et al, 2014; Liao et al, 2015). CHM is believed to maintain bone health, including: inhibition of inflammation, promotion of fracture healing, osteopenia prevention, and antiosteoporotic activities (Chow et al, 1982; Chen et al, 2005; Li et al, 2011; Ma et al, 2011; Xiang et al, 2011; Wong et al, 2013; He and Shen, 2014; Zhang et al, 2016; Hsiao et al, 2017; Wang et al, 2018c; Xi et al, 2018; Lee et al, 2019). These studies have encouraged the search for complementary therapy for the better management of bone-related diseases.…”
Section: Introductionmentioning
confidence: 99%